DEVELOPMENT AND VALIDATION OF METHODS FOR QUANTITATIVE DETERMINATION OF ACTIVE PHARMACEUTICAL SUBSTANCES IN NASAL SPRAY - M. V. Larskiy; A. E. Pozdnyakova; Z. D. Khadzhieva; D. I. Pozdnyakov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
Intranasal administration of H1-histamine receptor blockers may be a promising approach to the treatment of allergic rhinitis. Earlier, an original composition of a nasal spray containing fexofenadine hydrochloride and ammonium glycyrrhizinate and demonstrating a high level of therapeutic efficacy, was developed.The aim of the study was to develop and validate a method of the quantitative determination of active pharmaceutical ingredients fexofenadine hydrochloride and ammonium glycyrrhizinate in a spray for intranasal administration.Materials and methods. During the development and validation of the method of the fexofenadine hydrochloride and ammonium glycyrrhizinate quantitative determination in a nasal spray, the method of high performance liquid chromatography was used: a Dionex Ultimate 3000 UV chromatograph with a Luna C18 column (2) containing octadecylsilicagel with a 5 μm grain size as a sorbent. The analysis and validation procedures were performed in accordance with the requirements of the State Pharmacopoeia of the Russian Federation, the XIVth edition.Results. The study showed that for the simultaneous quantitative determination of fexofenadine hydrochloride and ammonium glycyrrhizinate, the optimal elution regime is a gradient mode with a mobile phase containing 50 mmol/L potassium dihydrogen phosphate solution with methanol (45:55), which ensured the separation of the components in the 20 minutes interval. The validation procedures showed that the developed methodology correspond to all the criteria of validity in terms of the following indicators: correctness, precision, specificity and linearity in the analytical area.Conclusion. The obtained results indicate the possibility of using the method of high-performance liquid chromatography in a gradient elution mode with a mobile phase of the composition of a 50 mmol/L solution of potassium dihydrogen phosphate with methanol (45:55) for the simultaneous quantitative determination of active pharmaceutical ingredients - fexofenadine hydrochloride and ammonium glycyrrhizinate as parts of a promising nasal spray for the allergic rhinitis treatment.